Anion-modulation in CoMoO4 electrocatalyst for urea-assisted energy-saving hydrogen production. (12th September 2022) - Guo, Yuhao; Liu, Xiaolei; Li, Yang; Ma, Fahao; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Cheng, Hefeng; Huang, Baibiao; Dai, Ying; Wang, Peng
Abstract: The anode oxygen evolution reaction (OER) is a delayed half-reaction of water splitting that requires a relatively high overpotential. Therefore, a more easily oxidized urea oxidation reaction (UOR) has been implemented to replace OER. Co–Mo-based bimetallic oxides have been recognized as interesting candidates for electrocatalytic water splitting due to their unique d electron configurations, but the low conductivity and limited active sites still hinder their development. Herein, we demonstrated that anion-modulation in CoMoO4 nanoplates as coupled hydrogen evolution reaction (HER) and UOR for convenient and efficient urea-assisted hydrogen-production system are demonstrated. The findings of the experiments show that nitrogen doping and phosphorus doping exhibit excellent activity toward alkaline HER and UOR, respectively. As a result, the N–CoMoO4 and P–CoMoO4 electrode exhibit low potentials of −0.062 V and 1.251 V (vs. RHE) to reach a current of 10 mA cm −2 for HER and UOR. The full urea electrolysis is driven by N–CoMoO4 ||P–CoMoO4 executes stably for 24 h at a low potential of 1.41 V. This is a unique anion-modulation method in electrocatalysts to combine hydrogen generation and sewage treatment, which could pave the way for the creation of long-term energy conversion systems. Graphical abstract: Image 1 Highlights: Modification of bimetallic oxides using anionic regulation strategies. The incorporation of nitrogen and phosphorus ions encourages HER and UOR, respectively. The electrocatalyst presents a low potential of 1.251 V at 10 mA cm −2 for UOR. The full urea electrolysis delivered the current density of 10 mA cm −2 at 1.41 V for 24 h.